(untitled) (SAARC Journal of Agriculture, 2014)
Field trials were conducted on sandy loam soil of Adisaptagram Block Seed Farm, Hooghly, West Bengal, India during three consecutive winter seasons of 2009-10, 2010-11 and 2012-13 to study the possibilities of calcium application in different proportions with primary nutrients in potato cultivation under irrigated conditions. The results indicated that all the biometrical parameters showed higher values when the potato crop received recommended dose of fertilizer (RDF) (200:66:124 kg N, P and K ha-1 respectively) plus 120 kg Ca ha-1 at planting which differed significantly from all other treatments tried in this investigation. Average yield of tuber was maximum (26.25 t ha-1) with RDF + 120 kg calcium application per ha at planting followed by RDF + 80 kg Ca (25.01 t ha-1). Higher dry matter content (15.14%) was obtained with RDF plus split application of Ca i.e. 40 kg at planting and remaining 40 kg at earthing up at par to 80 and 120 kg Ca at planting. On the other hand, yield of skin damaged tuber was higher (1.24 t ha-1) under the treatment having RDF + 40 kg calcium in two equal splits i.e. 20 kg at planting and 20 kg ha-1 at earthing up closely followed by RDF + 80 kg Ca ha-1, either single or split application (1.22 t ha-1). Therefore, combined application of RDF + Calcium (80-120 kg ha-1) has been proved to be the best option to get higher tuber yield of potato with good quality characteristics and higher monetary advantage. DOI: http://dx.doi.org/10.3329/sja.v12i1.21119 SAARC J. Agri., 12(1): 127-138 (2014)